2011
DOI: 10.1111/j.1365-2982.2011.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing dyspepsia‐related consultation: differences between a rural and an urban population

Abstract: Dyspepsia-related consultation varied significantly between urban and rural communities. Factors within the rural population, self-medication practices, and a low quality of life independently influenced dyspepsia-related consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In this study the M‐LDQ was validated in both primary and secondary care patients, as most patients consult at these levels of healthcare services . As the severity of patients' symptoms tends to differ between primary and secondary, or even tertiary care, a dyspepsia questionnaire assessing symptoms should ideally be validated in all settings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the M‐LDQ was validated in both primary and secondary care patients, as most patients consult at these levels of healthcare services . As the severity of patients' symptoms tends to differ between primary and secondary, or even tertiary care, a dyspepsia questionnaire assessing symptoms should ideally be validated in all settings .…”
Section: Discussionmentioning
confidence: 99%
“…In this study the M-LDQ was validated in both primary and secondary care patients, as most patients consult at these levels of healthcare services. 19 As the severity of patients' symptoms tends to differ between primary and secondary, or even tertiary care, a dyspepsia questionnaire assessing symptoms should ideally be validated in all settings. 13 A previous study in Hong Kong SAR, China did develop and validate a 'Chineselanguage' dyspepsia questionnaire, 20 but this was conducted in secondary-care patients only and it was not clear which type of Chinese language was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although healthcare systems in Asia and the West are known to differ, 6 other factors may be responsible for the variation in the economic impact of FD. Self-medication practices and lower healthcare consultation rates among rural Asians, 7 coupled with more aggressive management by clinicians in the US (40% had CT abdominal scans and 23% had surgery in Lacy et al's study), may lead to greater direct costs for FD in the West. Furthermore, socioeconomic differences between employees (81% in the US study 1 vs. 27.7% in the Malaysian study 4 with >US $ 10 000 annual income) are an obvious factor when considering indirect costs for FD due to work absenteeism.…”
mentioning
confidence: 99%
“…The study in Malaysia demonstrated that rural adults were more likely to seek medical consultation regarding their dyspepsia compared to urban adults, 41.4 and 28.7%, respectively [33]. The lower rates of consultation amongst urban adults with FD may in part be due to higher educational standards, with a greater awareness and a better understanding of the condition.…”
Section: Cultural Differences Which May Influence Fdmentioning
confidence: 99%
“…Based on the Rome II criteria, Mahadeva et al [33] demonstrated a significantly higher prevalence of FD among urban Malaysian adults (24.3%) compared to adults in a rural setting (14.5%), together with lower quality of life values among the former. The lower prevalence of FD among the rural population could not be explained by the observed socioeconomic differences between both communities, as low socioeconomic status has previously been suggested to be associated with dyspepsia.…”
Section: Cultural Differences Which May Influence Fdmentioning
confidence: 99%